2009
DOI: 10.1007/s11010-009-0312-1
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel PTEN-binding partners: PTEN interaction with fatty acid binding protein FABP4

Abstract: PTEN is a tumor suppressor with dual protein and lipid-phosphatase activity, which is frequently deleted or mutated in many human advanced cancers. Recent studies have also demonstrated that PTEN is a promising target in type II diabetes and obesity treatment. Using C-terminal PTEN sequence in pEG202-NLS as bait, yeast two-hybrid screening on Mouse Embryo, Colon Cancer, and HeLa cDNA libraries was carried out. Isolated positive clones were validated by mating assay and identified through automated DNA sequenci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 32 publications
0
40
0
1
Order By: Relevance
“…ACVRL1 (also known as ALK1) has well known importance in lung cancer, and ALK-rearrangement is a target in the treatment of lung cancers with this fusion. FABP4 interacts with PTEN, a well established tumor suppressor, and has been associated with a number of cancers [22]. Our GO analysis showed that our top mRNAs fell into a number of related molecular functions known to be associated with cancer.…”
Section: Discussionmentioning
confidence: 93%
“…ACVRL1 (also known as ALK1) has well known importance in lung cancer, and ALK-rearrangement is a target in the treatment of lung cancers with this fusion. FABP4 interacts with PTEN, a well established tumor suppressor, and has been associated with a number of cancers [22]. Our GO analysis showed that our top mRNAs fell into a number of related molecular functions known to be associated with cancer.…”
Section: Discussionmentioning
confidence: 93%
“…Mice with PTEN deletion in pancreatic cells show increase the β -cell mass because of both increased proliferation and reduced apoptosis. In particular, the relationship between PTEN function and adipocyte-specific fatty-acid-binding protein FABP4 is of interest in β -cell signaling [48]. The interaction of PTEN to FABP4 suggests a role for this phosphatase in the regulation of lipid metabolism and cell differentiation [49].…”
Section: Pi3k/akt/pten Pathway Involved In Type 2 Diabetesmentioning
confidence: 99%
“…Mice with PTEN deletion in pancreatic cells show an increase in the β-cell mass because of both increased proliferation and reduced apoptosis. In particular, the relationship between PTEN function and adipocyte-specific fatty acid-binding protein FABP4 is of interest in β-cell signaling [39]. The interaction of PTEN to FABP4 suggests a role for this phosphatase in the regulation of lipid metabolism and cell differentiation [40].…”
Section: Introductionmentioning
confidence: 99%